PEMODELAN KERUSAKAN MESIN BUBUT UNTUK ESTIMASI BANYAKNYA JUMLAH KERUSAKAN DAN ESTIMASI BIAYA PERAWATAN MESIN BUBUT DENGAN MEMPERHATIKAN FAKTOR INFLASI DITINJAU DARI ASPEK AKTUARIA - Bustami Bustami; Nurhazana Nurhazana (Politeknik Negeri Bengkalis, 2018)
The purpose of this research is to determine the Distribution Failure of Krisbow KW15-979 Machine Tool and also to determine the estimated cost of replacement of machine parts by taking into account the inflation factor, and to predict whether it is profitable or not if the lathe repair service is offered to a company that offering repair and maintenance services insurance of lathe. From the data obtained, the probability distribution of engine failure of Krisbow KW15-979 is Weibull distribution with Parameter scale (α) of 2.9868 in the calendar age is year, while the form parameter (β) is 1.6817 and the distribution of component replacement cost is obtained with normal distribution with parameters σ = 73607,0 μ = 1.2439E + 5. From the calculation and analysis of data for the first ten years buying insurance for the lathe maintenance service is not needed because expense cost is small and estimated amount of failure also small and there is also a minor damage can be handled by laboratory manpower of State Polytechnic of Bengkalis to repair and maintenance .so, when the lathe insured in the first year to the company that offers maintenance and repair insurance virgin lathe considered unprofitable.